From Scottsboro to Munich : race and political culture in 1930s Britain - Pennybacker, Susan D. (Princeton Univ. Press, 2009)
Presenting a portrait of engaged, activist lives in the 1930s, this text follows a global network of individuals and organizations that posed challenges to the racism and colonialism of the era.